Kebijakan Dinas Perhubungan Kota Pekanbaru dalam Mengatasi Kemacetan Lalu Lintas di Kota Pekanbaru - Azzahra Marsanda; Ratna Dewi (Yayasan Almanar Pujud, 2025)
Traffic congestion in Pekanbaru City has become a serious problem along with the growth in the number of vehicles and low awareness of road users. This study aims to analyze the policy of the Pekanbaru City Transportation Agency in overcoming congestion, by emphasizing three main indicators: legitimate government authority in formulating public policies, general policies for the benefit of the community, and the role of the government in ensuring that policies can be implemented effectively. The method used is a descriptive qualitative approach with observation, documentation, and interview techniques. The results of the study indicate that the Transportation Agency's policy has reflected the three indicators, although it still faces obstacles such as limited personnel and coordination between institutions. Therefore, strengthening institutions and increasing public awareness are important factors in realizing smooth traffic in Pekanbaru City.